AN ANALYSIS OF TEACHER TALK MANAGEMENT AT SENIOR HIGH SCHOOL - Kurnia, Muhsona Ayu; Samtidar, Samtidar; Muliati, A. (Universitas Negeri Makassar, 2023)
This study aimed to find out the kinds and functions of teacher talk management used in the English teaching process at SMA Tut Wuri Handayani Makassar. “This study used qualitative research design. The data of this research were observation checklists, interviews and video recordings to support them. The subject of this study was one English teacher who taught in different classes, the classes were from XI MIA and XI IIS. The result of the research found that (1) Teacher talk management used by teacher MJ’s learning process in the classroom is classified into 3 parts of the talk management process, which parts consist of starting the lesson, running the lesson, dan ending the lesson. Starting the lesson were entered the class, everyday greetings, took the register and started something new. Running the lesson was getting down to work, making things clear, sequencing activities, checking progress, and stopping. Ending the lesson was checking the time, setting homework, stopping work, making announcements, saying goodbye and clearing the class. (2) The functions of teacher talk management that were said by the English teacher were conveying information, delivering lessons in a structured way, and managing or arranging communication. In conclusion, the analysis of teacher talk management in the classroom was beneficial for teachers to plan and conduct enhanced learning situations.